Development Strategy for G-Land Beach as A Potential Premier Surfing Beach in Indonesia (The Indonesian Journal of Business Administration, 2013)
Tourism in Indonesia is an important component of the Indonesian economy as well as a significant source of its foreign exchange revenues and job creation. For Indonesia economy, In 2011 tourism contributed of Rp. 437.25 trillion to the Gross Domestic Product (GDP) or 13.8% of the total GDP of Indonesia (Source: BPS, 2012). GDP growth of tourism since 2001 had always showed a higher growth rate than the national GDP, which in 2011 tourism GDP growth reached 9.18%, while only 6.5% of national GDP (Source: BPS, 2012) . In terms of foreign exchange, foreign exchange earnings from tourism were the fourth largest contributor, after oil and gas, palm oil and processed rubber(Ministry of Tourism and Creative Economy, 2012)Plekung beach or known as the G-Land is one of the best surfing beaches in Indonesia. G-Land is known not only as a surfing beach because of the big wave, but also an exotic tourism area. The beach is located at Alas Purwo National Park that has beautiful panorama and rich of biodiversity. Even so, the name G-Land in the eyes of the tourists is still low, only known by professional surfers. Several issues for G-Land are lack of promotion and tourism products. Besides that, infrastructure problems such as inadequate accommodation facilities and difficult access to G-Land make this a problem more complicated. These research objectives are for planning the development concept of G-Land beach and formulating the policies and strategies to unleash their potential into the market to one of exciting tourism destination. It is related to increase G-Land’s brand awareness as a prime surfing spot in Indonesia and to encourage expansion of investment by private sectors with increased foreign direct investment (FDI) to G-Land Tourism Area, and to give favorable impact on the economy and the industry. This journal gave some recommendation for G-Land stakeholder in term of promotion strategy for short to medium term and Tourism Area Development Master Plan strategy for long term. To achieve these goals, four key strategies have been identified such as International level Surfing Event, Promotion Programs and Business Cooperation Programs and infrastructure and tourism area development.